2011
DOI: 10.1007/s10620-010-1555-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Perihepatic Lymphadenopathy in Patients with Chronic Hepatitis C Infection

Abstract: Presence of PLNE in patients with chronic HCV infection is strongly associated with subclinical cirrhosis. However, PLNE does not independently predict the progression of liver disease to decompensated cirrhosis and/or death in HCV-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…It should be noted that controversy still exists regarding whether PLNE could be associated with hepatocellular damage or liver fibrosis in patients with chronic HCV infection . These results raise a possibility that the clinical significance of PLNE may be distinct regarding the association with hepatitis activity between chronic HBV infection and chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that controversy still exists regarding whether PLNE could be associated with hepatocellular damage or liver fibrosis in patients with chronic HCV infection . These results raise a possibility that the clinical significance of PLNE may be distinct regarding the association with hepatitis activity between chronic HBV infection and chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Perihepatic lymph node enlargement (PLNE) is frequently observed in patients with chronic liver disease, especially in those with hepatitis C virus (HCV) infection . Although some studies have reported that PLNE was associated with inflammatory activity, stage of liver fibrosis or hepatitis viral load, such associations were inconsistent among other studies, suggesting that the clinical significance of PLNE in HCV infection has not been fully established yet. We have recently reported that PLNE is negatively associated with the response to interferon (IFN)‐based treatment or development of HCC in patients with chronic hepatitis C (CHC) .…”
Section: Introductionmentioning
confidence: 99%
“…However, controversy still exists regarding the association with hepatocellular damage or liver fibrosis in patients with chronic HCV infection. [9][10][11][12]14,16,17 Further study with larger samples including meta-analysis or further basic research is needed to clarify this point.…”
Section: Discussionmentioning
confidence: 99%
“…Perihepatic lymph node enlargement (PLNE) is an ultrasound (US) finding frequently observed in patients with chronic liver disease, especially in those with HCV. Although some studies have reported that PLNE was associated with inflammatory activity, stage of liver fibrosis or hepatitis viral load, such associations are inconsistent among other studies, suggesting that the clinical significance of PLNE in HCV infection has not been fully established yet. We have previously reported that PLNE is negatively associated with the response to interferon‐based treatment or development of HCC in patients with chronic hepatitis C (CHC) and also reported higher prevalence of PLNE in patients with chronic hepatitis B .…”
Section: Introductionmentioning
confidence: 97%
“…P ERIHEPATIC LYMPH NODE enlargement (PLNE), usually detected by abdominal ultrasonography, is known as a common finding in patients with chronic liver disease, 1 especially in those with hepatitis C. 2,3 Although PLNE in chronic hepatitis C is reportedly associated with inflammatory activity, stage of liver fibrosis [3][4][5][6][7] or hepatitis C viral load, 8 inconsistent findings have been reported, 2,4,9 suggesting that the clinical significance of PLNE in chronic hepatitis C has not been fully under-stood yet. PLNE in chronic hepatitis C has long been assumed to reflect an immunological response of the host.…”
Section: Introductionmentioning
confidence: 99%